PENGARUH ETIKA, BEBAN KERJA, PENGALAMAN AUDIT DAN SKEPTISISME PROFESIONAL TERHADAP PENDETEKSIAN KECURANGAN (Studi Kasus pada Kantor Akuntan Publik Di Wilayah Tangerang dan Tangerang Selatan): bahasa indonesia - Tri Purwanti (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
This study aims to determine the effect of ethics, workload, audit experience and professional skepticism on fraud detection (a case study at a public accounting firm in Tangerang and South Tangerang). The data sampling technique was through direct questionnaires to respondents using non-probability sampling method with purposive sampling technique. The research population is auditors who work in 6 Public Accounting Firms and obtained as many as 72 auditors as samples in this study. Data analysis was started by using Microsoft Office Excel 2019, then testing the data using Partial Least Square (Smart-PLS) software version 3.3.9. Based on the results of the study, it can be concluded that ethics and workload have a positive and significant positive effect on fraud detection, while the variables of audit experience and professional skepticism, experience, and workload have no effect on fraud detection.